Investigation on the garnierite and limonite mixed laterite ore for recovery nickel - Zhou, Shiwei; Lu, Chao; Zhang, Ba; Li, Bo; Wei, Yonggang (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
Laterite, as an important resource of nickel, has become the focus of development and utilization. This study adopted the method of mixing ore (garnierite and limonite) to increase the recovery rate of nickel in garnierite ore. The phase transformation of the two ores were investigated during the heating process, dehydroxylation and recrystallization were observed and the iron oxides phase was transformed into iron-containing spinel finally. By changing the proportion of the two ores, increasing the iron content in the sample was beneficial to the reduction of nickel. Then, Fe2O3, Fe3O4 and Fe were used as the iron source to study the mechanism of the iron-bearing minerals in promoting the reduction of nickel. The results indicated that hematite and/or magnetite would react with amorphous silicate minerals to generate magnesioferrite and enstatite, thereby avoiding additional forsterite generation; moreover, the trevorite phase would be formed, which strengthens the aggregation of nickel and iron.
Keywords: Garnierite ore; Limonite ore; Reduction; Phase transformation